2021
DOI: 10.3390/ijerph18189811
|View full text |Cite
|
Sign up to set email alerts
|

Using Low-Cost Sensors to Assess Fine Particulate Matter Infiltration (PM2.5) during a Wildfire Smoke Episode at a Large Inpatient Healthcare Facility

Abstract: Wildfire smoke exposure is associated with a range of acute health outcomes, which can be more severe in individuals with underlying health conditions. Currently, there is limited information on the susceptibility of healthcare facilities to smoke infiltration. As part of a larger study to address this gap, a rehabilitation facility in Vancouver, Canada was outfitted with one outdoor and seven indoor low-cost fine particulate matter (PM2.5) sensors in Air Quality Eggs (EGG) during the summer of 2020. Raw measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Similar results were also seen in a 12 days study conducted in a retirement community, where Buczynska et al found no significant indoor sources of air pollution but did see a positive relationship between outdoor and Indoor Air Quality 5 . Another group recently published an investigation of a single healthcare building during a two‐month period of the 2020 wildfire season where they deployed two outdoor and seven indoor PM 2.5 sensors 41 . Their results indicate that PM 2.5 infiltrates the indoor space to a greater degree during a smoke event and is variable by location within the building.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were also seen in a 12 days study conducted in a retirement community, where Buczynska et al found no significant indoor sources of air pollution but did see a positive relationship between outdoor and Indoor Air Quality 5 . Another group recently published an investigation of a single healthcare building during a two‐month period of the 2020 wildfire season where they deployed two outdoor and seven indoor PM 2.5 sensors 41 . Their results indicate that PM 2.5 infiltrates the indoor space to a greater degree during a smoke event and is variable by location within the building.…”
Section: Discussionsupporting
confidence: 71%
“…5 Another group recently published an investigation of a single healthcare building during a two-month period of the 2020 wildfire season where they deployed two outdoor and seven indoor PM 2.5 sensors. 41 Their results indicate that PM 2.5 infiltrates the indoor space to a greater degree during a smoke event and is variable by location within the building.…”
Section: Discussionmentioning
confidence: 97%
“…Health facilities should continuously monitor and compare outdoor and indoor PM concentrations to assess the effectiveness of cleaner air interventions. 83 Changes in indoor pollutant concentrations can signal building managers to adjust HVAC systems and other interventions.…”
Section: Monitoringmentioning
confidence: 99%
“…With the inclusion of future climate data, northern BC LHAs score higher given the faster rate of warming being experienced relative to coastal and southern regions of the province. The inclusion of climate data is an increasingly important function of environmental exposures in BC given recent risks associated with flooding [ 33 ], wildfires [ 34 ] and extreme heat [ 35 ]. Notably, the inclusion of these and other variables in the BCEnviroScreen perhaps requires a change in moniker from a ‘pollution burden’ score to something that approximates a cumulative measure of ‘landscape burden’.…”
Section: Resultsmentioning
confidence: 99%